2017
DOI: 10.7150/ijms.21938
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Prognostic Value of ERCC1 and Thymidylate Synthase Expression and the Epidermal Growth Factor Receptor Mutation Status in Adenocarcinoma Non-Small-Cell Lung Cancer

Abstract: The present study evaluated the prognostic value of the epidermal growth factor receptor (EGFR) mutation status, and excision repair cross-complementation group 1 (ERCC1) and thymidylate synthase (TS) expression following intercalated tyrosine kinase inhibitor (TKI) therapy and platinum- and pemetrexed-based chemotherapies (subsequent second-line treatment) for patients with adenocarcinoma non-small-cell lung cancer (AC-NSCLC). In total, 131 patients with AC-NSCLC were enrolled. The EGFR mutation status and ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…TS is the critical enzyme that catalyzes the methylation of dUMP to dTMP with 5,10-methylenetetrahydrofolate as a cofactor. Therefore, it provides the intracellular de novo source of thymidylate, which is essentially required for DNA replication and repair ( 24 ). Studies have shown that overexpression of TS is believed to confer resistance to 5FU-based adjuvant chemotherapy, and has been considerably associated with the poor prognosis of the subset of aggressive solid tumors, including breast, lung, stomach, and colorectal cancer ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…TS is the critical enzyme that catalyzes the methylation of dUMP to dTMP with 5,10-methylenetetrahydrofolate as a cofactor. Therefore, it provides the intracellular de novo source of thymidylate, which is essentially required for DNA replication and repair ( 24 ). Studies have shown that overexpression of TS is believed to confer resistance to 5FU-based adjuvant chemotherapy, and has been considerably associated with the poor prognosis of the subset of aggressive solid tumors, including breast, lung, stomach, and colorectal cancer ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…We selected two CDH1 SNPs, including rs16260 (-160, C/A) in the promoter region and the intron 2 variant rs9929218 based on their potential involvement in the various cancer types 16 - 20 . Different associating factors relating to the mutations in EGFR were considered and analyzed as previously described 21 , 22 . Data obtained from medical record of each patient included demographics (age, gender), tobacco smoking status, and tumor staging and differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the diagnosis of highly symptomatic metastatic lung adenocarcinoma with a high tumor burden leading to organ compromise, systemic cytoreductive treatment was clearly indicated. Loss of thymidylate synthase expression predicted a good response to pemetrexed or other anti-folate agents, while the high tumor mutational burden and high PDL-1 expression predicted an excellent response to anti-PDL-1 antibodies [10][11][12][13]. Indeed, the prognosis of Stage IV non-small cell lung cancer in the modern age of immunotherapy is improved with a quadrupling of the historical 4% five year overall survival rate to 16% with immunotherapy [14].…”
Section: Wwwijcrioncologycommentioning
confidence: 99%